2011
DOI: 10.1007/s00005-011-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender Specific Differences in the Immune Response to Infection

Abstract: There are many instances where males and females differ in the susceptibility to infections. The reason for these differences in susceptibility is multifactorial. The primary cause is thought to be due to differences induced by sex hormones and their effects on gene expression as well as the immune system, but may also be due to innate physiological differences between males and females. This review summarizes gender specific differences seen in infections caused by bacteria, fungi, parasites and viruses. Ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 130 publications
(152 reference statements)
7
138
0
4
Order By: Relevance
“…Clinical and experimental researches have demonstrated naturally occurring gender differences in immune responses [1,2]. Interestingly, our and others' studies have shown that cells of males and females display several different features and behaviors [3][4][5].…”
Section: Introductionmentioning
confidence: 78%
“…Clinical and experimental researches have demonstrated naturally occurring gender differences in immune responses [1,2]. Interestingly, our and others' studies have shown that cells of males and females display several different features and behaviors [3][4][5].…”
Section: Introductionmentioning
confidence: 78%
“…EV-7 of a specifi c infection (Atkinson et al 2008, McClelland andSmith 2011). Leucocytozoon is a parasite with characteristic clinical phases including an initial acute phase followed by a latent or chronic infection (Valki ū nas 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models find that female mice show greater systemic resistance to pneumococci (Weiss et al, 1973; Kadioglu et al, 2011) and to many other (but not all) pathogens (McClelland and Smith, 2011). Epidemiologic studies of human pneumonia observe a greater incidence of community-acquired pneumonia in males (Gutiérrez et al, 2006) and show that males are at greater risk than females for pneumonia after admission to hospital after adjusting for other risk factors such as smoking and alcohol use (Offner et al, 1999; Andermahr et al, 2002; Gannon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%